Effectiveness of a practical multi-setting lifestyle intervention on the main BMI trajectories from childhood to young adulthood: A community-based trial - Parnian Parvin; Hasti Masihay-Akbar; Leila Cheraghi; Soha Razmjouei; Amirali Zareie Shab-khaneh; Fereidoun Azizi; Parisa Amiri (BMC, 2022)
Abstract Background Preventing overweight in childhood and subsequent stages of life is still a global challenge. Despite numerous relevant lifestyle interventions, data on their impact on different BMI change pathways over time is rare. The present study aimed to investigate the effect of a multi-setting lifestyle intervention on BMI trajectories from childhood to young adulthood. Methods A multi-setting lifestyle intervention at the school, family, and community levels have been conducted in the Tehran Lipid and Glucose Study framework. A total of 2145 children (4-18 years, 49% boys, and 18% intervention) were recruited for the baseline assessment and were followed through five follow-up examinations during a median of 16.1 years. Using a group-based trajectory model, BMI trajectories from childhood to young adulthood were identified, and their association with the implemented intervention was assessed. Results Four trajectory groups of BMI from childhood to young adulthood were identified, including Normal weight (41%), Young adulthood overweight (36%), Early childhood increasing overweight and adulthood obesity (19%), and Early childhood increasing obesity (4%). Only Young adulthood overweight and Early childhood increasing obesity were affected by the intervention and were concomitant with lower BMI levels than the control group, with the highest estimated effect in the latter (β=-0.52 and p = 0.018; β=-1.48 and p < 0.001, respectively). Conclusion The current findings indicate the highest effectiveness of a practical, healthy lifestyle intervention on those whose obesity started in the early years of life or youth. Our results could help policymakers and planners design more targeted lifestyle modification and weight control interventions. Trial registration This study is registered at Iran Registry for Clinical Trials, a WHO primary registry ( http://irct.ir ). The Iran Registry for Clinical Trials ID and date are IRCTID:IRCT138705301058N1, 29/10/2008.